Safety of Lorlatinib in Patients with Unresectable Advanced ALK-Positive Non-Small-Cell Lung Cancer Previously Treated with ALK Inhibitors: A Single-Arm, Open-Label, Phase IV Study in India - Ullas Batra; Vineet G. Gupta; Nirmal Raut; Tushar Patil; Harsha Panchal; Nikhil Ghadyalpatil; Anand Pathak; Chirag Desai; Shailesh Bondarde; Minish Jain; Christian Russel Reyes; Shyam Parvatini; et al. (Indian Journal of Medical and Paediatric Oncology, 2025)
Lorlatinib is approved in India for patients with previously treated anaplastic lymphoma kinase (ALK)–positive advanced or recurrent non-small-cell lung cancer (NSCLC). Owing to the limited number of Indian patients in phase I/II and III studies, a postapproval study was conducted to report the safety and efficacy of lorlatinib in this patient population. In this phase IV study, patients with unresectable advanced and/or recurrent ALK-positive NSCLC resistant or intolerant to ≥1 prior ALK inhibitor were treated with lorlatinib. The primary endpoint was investigator-assessed incidence of treatment-related adverse events (TRAEs). Secondary endpoints were investigator-assessed objective response rate (ORR), intracranial ORR, duration of response (DOR), and intracranial DOR. Among the 100 patients enrolled, the most frequently reported TRAEs were hypertriglyceridemia (57%), hypercholesterolemia (57%), and weight increase (38%). The confirmed ORR and intracranial ORR by the investigator were 41% (95% confidence interval [CI]: 31.9–50.8%) and 36% (95% CI: 24.5–48.8%), respectively. The median systemic and intracranial DORs were not reached. The safety profile of lorlatinib was consistent with that reported in the phase I/II study. Lorlatinib showed a clinically meaningful improvement in ORR and intracranial ORR in patients with unresectable advanced ALK-positive NSCLC. These results support the use of lorlatinib in India for patients with previously treated ALK-positive advanced NSCLC.